2018
DOI: 10.1155/2018/4343196
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Gut Microbial Composition and Meat Flavor of Two Chicken Breeds in Different Rearing Patterns

Abstract: The objective of the study is to compare the effects of free-range (FR) and cage-range (CR) breeding on gut microbiota and flavor compounds of Caoke (C) and Partridge Shank chickens (Q). A total of 120 experimental chickens were assigned to FR group and CR group; each group contain both 30 Caoke chickens and 30 Partridge Shank chickens. At 154 d old, 12 chickens of each group were selected and their cecal contents were extracted and examined for the composition of gut microbiota by illumina sequencing of the V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 45 publications
(45 reference statements)
3
21
0
1
Order By: Relevance
“…This represents the first report by our team of a relative abundance of Fusobacteria > 1% ( Zhu et al, 2020a , b ). Fusobacteria were detected in Partridge Shank chickens under free-range breeding conditions, but not in chickens fed in cages ( Sun et al, 2018 ), while Elokil et al reported an abundance of about 0.011%–0.060% for Fusobacteria sequenced in laying chickens housed in individual cages inside an enclosed farm ( Elokil et al, 2020 ). These results suggest that Fusobacteria may be a normal component of the intestinal microbiota, even though some studies failed to detect its relative abundance.…”
Section: Discussionmentioning
confidence: 99%
“…This represents the first report by our team of a relative abundance of Fusobacteria > 1% ( Zhu et al, 2020a , b ). Fusobacteria were detected in Partridge Shank chickens under free-range breeding conditions, but not in chickens fed in cages ( Sun et al, 2018 ), while Elokil et al reported an abundance of about 0.011%–0.060% for Fusobacteria sequenced in laying chickens housed in individual cages inside an enclosed farm ( Elokil et al, 2020 ). These results suggest that Fusobacteria may be a normal component of the intestinal microbiota, even though some studies failed to detect its relative abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Fusobacteria activate host inflammatory responses to protect against pathogens that promote tumor growth ( Kelly et al., 2018 ). Moreover, in a recent study, Sun et al. (2018) have compared the gut microbial composition of 2 chicken breeds in different rearing patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences in the cecum microbiota in Dagu chicken appeared under free range and cage raising feeding modes [16]. Different breeds of chickens affect the structure of intestinal microbiota and the flavor of chickens, which might be caused by the different diets and feeding modes [32].…”
Section: Discussionmentioning
confidence: 99%